2023
DOI: 10.1111/aogs.14645
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for proton therapy during pregnancy

Abstract: During pregnancy, the use of radiation therapy for cancer treatment is often considered impossible due to the assumed associated fetal risks. However, suboptimal treatment of pregnant cancer patients and unjustifiable delay in radiation therapy until after delivery can be harmful for both patient and child. In non‐pregnant patients, proton‐radiation therapy is increasingly administered because of its favorable dosimetric properties compared with photon‐radiation therapy. Although data on the use of pencil beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The findings of this study are consistent with previous studies that have shown the superiority of proton therapy in reducing the dose to normal tissues 20–25 . Our study demonstrates that intensity‐modulated proton therapy (IMPT) has the potential to significantly minimize fetal dose exposure during radiation therapy for pregnant patients with brain tumors, even when accounting for neutron dose generated from protons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study are consistent with previous studies that have shown the superiority of proton therapy in reducing the dose to normal tissues 20–25 . Our study demonstrates that intensity‐modulated proton therapy (IMPT) has the potential to significantly minimize fetal dose exposure during radiation therapy for pregnant patients with brain tumors, even when accounting for neutron dose generated from protons.…”
Section: Discussionsupporting
confidence: 90%
“…This poses challenges, particularly for the small proton therapy centers that are increasingly emerging. Hence, it is crucial to underscore the importance of collaborative case studies and the collective compilation of a comprehensive database, which ultimately benefits all patients 20–25 …”
Section: Introductionmentioning
confidence: 99%
“…Most of the time, the benefits of a precise diagnosis outweigh any possible risks associated with radiation (Michalet et al, 2022). When a fetus is in or close to a radiation beam during an examination that is at the higher end of the diagnostic dosage range, the risk-benefit equation requires limiting procedures and doses as much as practical while maintaining enough information to provide a correct diagnosis (Blommaert et al, 2024). This can be achieved by tailoring the examination to minimize the number of radiographs needed or, in the case of nuclear medicine, by promoting hydration and prompt radiopharmaceutical voiding through the urinary tract to minimize exposure to the fetus (Lowe, 2004).…”
Section: Reducing Fetal Radiation In Pregnancymentioning
confidence: 99%
“… 10 In this context, proton radiotherapy is a recent development that allows considerable reduction in fetal exposure, although standardization is needed. 12 …”
Section: Treatment Approach To Pregnancy‐related Breast Cancermentioning
confidence: 99%